PENENTUAN OPTIMASI RUTE DISTRIBUSI MENGGUNAKAN ALGORITMA CLARKE AND WRIGHT SAVINGS DAN ALGORITMA NEAREST NEIGHBOR STUDI KASUS PETERNAKAN AYAM PETELUR ADI FARM - Radhinal Sa’id Riginianto; Widya Setiafindari (JURNAL ILMIAH NUSANTARA, 2024)
The distribution of chicken eggs by Adi Farm does not take into account the distance to reach customers and distribution costs. There are 11 customers with a total distance traveled of 122.4 km and distribution costs of IDR 292,400. The method used to solve this problem uses the Clarke and Wright Savings algorithm and the Nearest Neighbor Algorithm. Based on the result of calculations using the Clarke and Wright Savings algorithm method, the result was a distance of 106.5 km with a total cost of IDR 276,500. Meanwhile, using the Nearest Neighbor algorithm method, the distance obtained was 124.4 km with a total distribution cost of IDR 294,400. Using the Clarke and Wright Savings algorithm method shows a distance saving of 12.99%.